Translation-Targeting RiPPs and Where to Find Them - Dmitrii Y. Travin; Dmitrii Y. Travin; Dmitry Bikmetov; Dmitry Bikmetov; Konstantin Severinov; Konstantin Severinov; Konstantin Severinov; Konstantin Severinov (Frontiers in Genetics, 2020)
Prokaryotic translation is among the major targets of diverse natural products with antibacterial activity including several classes of clinically relevant antibiotics. In this review, we summarize the information about the structure, biosynthesis, and modes of action of translation inhibiting ribosomally synthesized and post-translationally modified peptides (RiPPs). Azol(in)e-containing RiPPs are known to target translation, and several new compounds inhibiting the ribosome have been characterized recently. We performed a systematic search for biosynthetic gene clusters (BGCs) of azol(in)e-containing RiPPs. This search uncovered several groups of clusters that likely direct the synthesis of novel compounds, some of which may be targeting the ribosome.